2021
DOI: 10.1093/humrep/deab246
|View full text |Cite
|
Sign up to set email alerts
|

The relation of number of childbirths with age at natural menopause: a population study of 310 147 women in Norway

Abstract: STUDY QUESTION Does age at natural menopause increase with increasing of number of childbirths? SUMMARY ANSWER Age at menopause increased with increasing number of childbirths up to three childbirths; however, we found no further increase in age at menopause beyond three childbirths. WHAT IS KNOWN ALREADY Pregnancies interrupt ovulation, and a high number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Although several studies have also observed this association, 42-45 others report no such relationship or an inverse association between late age at last childbirth and delayed onset of menopause 46 . Parity, however, has largely been reported to be positively associated with later onset of menopause 46-49 . Given that in the current study, women who had birth at later ages tended to have high parity suggests that childbirth at later ages may be a sign of delayed reproductive and somatic aging, and the fewer cumulative menstrual cycles that such parous women have due to multiple pregnancies may be associated with a larger reserve of oocytes and longer exposure to estrogen therefore delaying the onset of menopause 19,46 .…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Although several studies have also observed this association, 42-45 others report no such relationship or an inverse association between late age at last childbirth and delayed onset of menopause 46 . Parity, however, has largely been reported to be positively associated with later onset of menopause 46-49 . Given that in the current study, women who had birth at later ages tended to have high parity suggests that childbirth at later ages may be a sign of delayed reproductive and somatic aging, and the fewer cumulative menstrual cycles that such parous women have due to multiple pregnancies may be associated with a larger reserve of oocytes and longer exposure to estrogen therefore delaying the onset of menopause 19,46 .…”
Section: Discussionmentioning
confidence: 44%
“…46 Parity, however, has largely been reported to be positively associated with later onset of menopause. [46][47][48][49] Given that in the current study, women who had birth at later ages tended to have high parity suggests that childbirth at later ages may be a sign of delayed reproductive and somatic aging, and the fewer cumulative menstrual cycles that such parous women have due to multiple pregnancies may be associated with a larger reserve of oocytes and longer exposure to estrogen therefore delaying the onset of menopause. 19,46 Thus, compared with primiparous women with childbirth at older ages, parous women with younger ages at first birth or nulliparous women, parous women with late age at last childbirth may have slower ovarian aging resulting in them benefiting longer from ovarian secretion of steroid hormones, including estrogen, progesterone, androgens, and various cytokines that affect the function of several reproductive organs, as well as other organs of the cardiovascular, musculoskeletal, and immune systems.…”
Section: Discussionmentioning
confidence: 71%
“… 25 We identified year of birth (birth cohort), place of birth, number of childbirths, educational level, body mass index (BMI, kg/m 2 ) and smoking habits as possible confounders since these factors have been associated with alcohol consumption 26–29 and age at menopause. 1 , 30 , 31 Year of birth and BMI were included as continuous variables in the data analyses, whereas we treated place of birth (Norway, Europe, outside Europe), number of childbirths (0, 1, 2, ≥3), educational level (<high school, high school, <4 years of university, ≥4 years of university) and smoking habits (never smoker, former smoker, smoker) as categorical variables.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the rate of ovarian aging was unexpectedly accelerated. At the age of 51 years, the number of follicles decreased to 1000, which can be used as a threshold for menopause, as it corresponds to the average age of menopause in women (93,102).…”
Section: Functional Aspects Of the Ovarymentioning
confidence: 99%